DISCOVERY LEARNING FOR DIGITAL READING: DESIGNING A CONSTRUCTIVE-RESPONSIVE MODEL AND ITS INSTRUCTIONAL IMPLICATIONS - Ida Hamidah; Fahrus Zaman Fadhly; Siti Sa'diah (Indonesian EFL Journal, 2025)
The rise of digital reading in higher education has reshaped how students engage with texts, requiring critical navigation and evaluation of multimodal, non-linear information. Despite the growing complexity of digital texts, current instructional models often lack the responsiveness needed to support student comprehension in digital environments. Existing approaches are either too rigid or fail to integrate pedagogical strategies that account for digital reading challenges. This study aimed to design a Discovery Learning-based instructional model grounded in Constructive-Responsive principles to enhance digital reading skills among university students. Using a research and development approach, the study applied the 4D model—Define, Design, Develop, and Disseminate—with data collected through expert validation, field trials, and student feedback at four private universities in West Java, Indonesia. The resulting model integrates six stages of Discovery Learning with adaptive scaffolding, allowing students to explore digital texts actively while developing metacognitive regulation and critical evaluation skills. The model improved students’ comprehension, source evaluation, and digital navigation abilities. This instructional model addresses gaps in digital reading pedagogy by offering a flexible and student-centered framework. It holds potential for broad application in digital literacy instruction and may inform future curriculum and instructional design in higher education.